Treading in the Sea of Data. - Yonck, Richard (Futurist)
The article offers insights on a variety of technologies, from nanotechnology to genetics to search engines, that may save people from drowning and even help to thrive in data. It relates that high-speed wireless technologies will soon enable to access information from almost any location at speeds approaching those of wired networks. It claims that lifelogging could exacerbate data problem. The Semantic Web conceived by the father of the World Wide Web Tim Berners-Lee aims to take information that is currently only machine readable and make it machine understandable.